PENERAPAN GOOGLE CLASSROOM PADA PEMBELAJARAN BILANGAN BERPANGKAT DAN BENTUK AKARDI SMA NEGERI 2 TONDANO - Nofanti Yustina; Victor R. Sulangi; James U. L. Mangobi (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This study aims to develop learning rank numbers and root shapes with Google Classroom in SMA Negeri 2 Tondano and to determine the quality of learning rank numbers and root shapes with Google Classroom in SMA Negeri 2 Tondano seen from the aspect of validity, practicality, and effectiveness. This research is a Research and Development (R & D) using a 4D development research model consisting of Define, Design, Develop and Desseminate. The percentage of validity of the results of the fourth expert assessment in a row is 89.28%, 83.57%, 92.14% and 87.85% where the results of the second expert assessment are on valid criteria while the results of the first expert assessment. the third and fourth are on very valid criteria. The practicality of learning numbers and root forms with Google Classroom based on the average student response result is 86% with very practical criteria, while the teacher response result is 92% with very practical criteria. the effectiveness of learning numbers rank and root form with Google Classroom based on student learning outcomes test with the percentage of completeness is 83.33% with very effective criteria. In conclusion learning numbers rank and root forms with Google Classroom developed valid, practical, and effective for use in the learning process at school.